Perlindungan Perempuan dan Anak Dalam Prespektif Filsafat Hukum - Safrudin; Rumainur (Universitas Ngudi Waluyo, 2022)
The Indonesian government has established various institutions as an effort to protect human rights and justice for women and children, including the National Commission on Violence Against Women, the National Commission on Human Rights, the Witness and Victim Protection Agency and the Ombudsman. Even though Indonesia has ratified the CEDAW Convention plus strengthened through various human rights institutions, violence against women and children is still massive in Indonesia. In this writing, the research method used by the author is normative juridical. The results of this study show that violence against women and children will continue to occur if the government is not really serious in making regulations and implementing the protection of women and children. Apart from that, public awareness is needed regarding the nature of being human, that all human beings are equal. Abstrak Pemerintah indonesia telah membentuk berbagai institusi sebagai upanya perlindungan HAM dan keadilan terhadap kaum perempuan dan anak, diantaranya Komnas Perempuan, Komnas HAM, Lembaga Perlindungan Saksi dan Korban dan, Ombudsman. Meski indonesia telah meratifikasi Konvensi CEDAW ditambah penguatan melalui berbagai lembaga HAM, kekerasan terhadap perempuan dan anak masih masif terjadi di Negara Indonesia. Dalam penulisan ini , metode penelitian yang digunakan oleh penulis adalah normatif yuridis. Adapun hasil penelitian ini bahwa kekerasan terhadap perempuan dan anak akan terus terjadi apabila pemerintah tidak benar-benar serius dalam membuat regulasi dan implementasi terhadap perlindungan perempuan dan anak, selain daripada itu dibutuhkan kesadaran masyarakat terkait hakikat menjadi manusia bahwa semua manusia itu sama kedudukannya.